2017
DOI: 10.1002/clc.22687
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study to evaluate the safety and LDL cholesterol–lowering effects of RG7652, a fully human monoclonal antibody against proprotein convertase subtilisin/kexin type 9

Abstract: Background Proprotein convertase subtilisin/kexin type 9 (PCSK9) downregulates low‐density lipoprotein (LDL) receptors, thereby leading to a rise in circulating LDL cholesterol (LDL‐C). RG7652 is a fully human monoclonal antibody against PCSK9. This placebo‐controlled, phase 1 ascending‐dose study in healthy subjects evaluated the safety of RG7652 and its efficacy as a potential LDL‐C–lowering drug. Hypothesis Anti‐PCSK9 antibody therapy safely and effectively reduces LDL‐C. Methods Subjects (N = 80) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A phase 1 study of RG7652 (Roche Genentech), another fully human monoclonal antibody, revealed a substantial and sustained reduction of LDL-C, with an acceptable safety profile and minimal immunogenicity. 28 In conclusion, PCSK9 inhibitors are useful for the treatment of diabetic dyslipidemia. Research regarding the risk of developing diabetes mellitus following long-term exposure to PCSK9 inhibitors is warranted.…”
Section: Perspectives Of Nonstatin Therapy In Treatment Of Diabetic Dmentioning
confidence: 97%
See 1 more Smart Citation
“…A phase 1 study of RG7652 (Roche Genentech), another fully human monoclonal antibody, revealed a substantial and sustained reduction of LDL-C, with an acceptable safety profile and minimal immunogenicity. 28 In conclusion, PCSK9 inhibitors are useful for the treatment of diabetic dyslipidemia. Research regarding the risk of developing diabetes mellitus following long-term exposure to PCSK9 inhibitors is warranted.…”
Section: Perspectives Of Nonstatin Therapy In Treatment Of Diabetic Dmentioning
confidence: 97%
“…26 Because these anti-PCSK9 antibodies have already demonstrated their importance, a great effort has been made by pharmaceutical companies to develop additional PCSK9 inhibitors. 27 In 2017, Pfizer Inc. 27 and Genentech Inc. 28 reported the efficacy and safety of two new anti-PCSK9 antibodies, bococizumab 27 and RG7652 28 ; however, those trials were not specifically designed for subjects with diabetic dyslipidemia. It should be emphasized that different types of anti-PCSK9 drugs have distinct mechanisms of action.…”
Section: Perspectives Of Nonstatin Therapy In Treatment Of Diabetic Dmentioning
confidence: 99%
“…Findings from PCSK9 monoclonal antibodies research did not find excess in muscle adverse symptoms or rise in creatinine kinase or liver enzyme levels which are commonly associated with statin therapy. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 ] Nasopharyngitis and mild self-limited injection site reactions (e.g., itching, redness, and swelling) are considered the most frequent adverse reactions. [ 4 59 62 ]…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Although bococizumab development was stopped in 2016, [ 7 ] trials on other potential monoclonal antibodies are ongoing with encouraging initial results. [ 8 9 10 11 ] The efficacy and the safety of PCSK9 monoclonal antibodies in the treatment of hypercholesterolemia will be discussed in this overview.…”
Section: Introductionmentioning
confidence: 99%
“…After the completion of six bococizumab studies, an unexpected attenuation of effect on LDL-C over time was observed, in addition to high rates of injection-site reaction due to high immunogenicity 9 . However, the development of new investigational monoclonal antibodies to inhibit PCSK9 is well under way with promising initial results [10][11][12][13] . This review will discuss the efficacy and safety profile of PCSK9 monoclonal antibodies or inhibitors in the treatment of familial and non-familial hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%